Oliver's work is not accurate. The equation (x+3)(x+4)=0 correctly factors the quadratic, and according to the Zero Product Property, each factor should be set equal to zero.
In the table, the factor (x+3) is incorrectly replaced with (x−3) in the second row. The correct equation should be:
- From (x+3)(x+4)=0, the factors are:
- x + 3 = 0 ➔ x = -3
- x + 4 = 0 ➔ x = -4
So the correct values of x that satisfy the equation are x = -3 and x = -4, not x = 3 and x = -4 as listed.
Therefore, the correct response is:
No, x−3=0 in the second row should be x+3=0.